New product development : - Annacchino, Marc A. (Elsevier, 2003)
This comprehensive and detailed book is a practical guide to the process of New Product Development from initial concept and corporate goals assessment through marketing, planning, development, manufacturing and product management. It contains over 200 illustrations with 52 actual tools needed to execute an actual program. On the accompanying CD-ROM version, these tools are embedded in the text for presentation to the reader. Embedded hyperlinks allow the reader to jump to a special "sandbox" which will allow them to apply the concepts presented in the text directly to their development program and save them as part of their filing system, providing the actual framework for practitioner use.